Multi-Conference Rooms: Architectural and Technological View - Coelho, Luiz; Longoni, Guilherme; Cecagno, Felipe; Ciuffo, Leandro; Duarte, Renato; Roesler, Valter (My University, 2015)
Meeting rooms, as well as classrooms, can be transformed in multimedia spaces that amplify collaboration and education. Computers, projectors, large displays, videoconference systems and wi-fi networks are examples of Information Technologies infrastructures commonly installed in modern rooms. However, the investment to transform a traditional classroom in a digital learning space must be spent efficiently to justify the invested resources. The cost of any physical space depends on how often it is used. For example, a US$100,000.00 regular classroom can cost more than a US$500,000.00 one. How? Suppose the cheaper room is used eight hours a month, while the more expensive one is used eighty hours a month. Over five years (or 60 months), the per-hour cost of the cheaper room will be US$100,000.00 / (60 * 8) = US$208.33, while the per-hour cost of the more expensive one will be US$500,000.00 / (60 * 80) = US$104.17, i.e., half the cost of the first. The bottom line is that keeping an idle physical structure has a high associated cost. The objective of this paper is to present an architectural and technological view of a new system called "multipresence" which adapts to various physical environment settings, and enables the interoperability of various technologies.
Keywords: Mobile conferencing; ultra-high definition; web conferencing; telepresence; multipurpose rooms